Significantly Increased Rates of Primary Cesarean Delivery in Various Co-Morbid Conditions [22Q]. (May 2016) - Duffy, Jennifer; Penfield, Christina; Fong, Alex; King, Ebony; Pan, Deyu; Ogunyemi, Dotun
Abstract : INTRODUCTION: To characterize primary cesarean delivery (CD) rates in term, singleton, vertex pregnancies in the setting of various co-morbid obstetrical/medical conditions. METHODS: We performed a retrospective cohort study comprising all singleton, vertex, term pregnancies deliveries in California from 2001–2009. Co-morbid obstetrical/medical conditions were defined as presence of one or more of the following: asthma, chronic hypertension, diabetes, preeclampsia/eclampsia, thyroid disease, cardiac disease, obesity, lupus, or tobacco use. We excluded cases of malpresentation, preterm delivery, and fetal death. Cases of primary CD, as well as other delivery-related morbidities were identified via ICD-9-CM code. Logistic regression was performed to adjust for potential confounders. RESULTS: Out of over 4.5 million deliveries, co-morbidities were identified in 13% of all subjects. The following conditions were all associated with a significant adjusted increase in primary CD (ranging from 18.4–25.7% vs a baseline rate of 15%): tobacco use, lupus, obesity, cardiac disease, thyroid disease, gestational diabetes, and asthma. Subjects with mild preeclampsia, severe preeclampsia, and obesity had an approximately 30% chance of undergoing primary CD. The primary CD rate in those with eclampsia, severe preeclampsia, and macrosomia exceeded 50%. CONCLUSION: Several conditions are associated with an increased primary CD rate. Conditions such as macrosomia and severe preeclampsia/eclampsia have a strikingly high primary CD rate (>50%). Further study should be done on whether these higher primary CD rates are due to appropriate obstetrical indications. These patients comprise a significant proportion of the population; thus, prevention of primary CD in these medical co-morbidities is an area for targeted quality improvement.